Local magnetism and magnetoelectric effect in HoMnO3 studied with muon-spin relaxation - Lewtas, H; Lancaster, T; Baker, P; Blundell, S; Prabhakaran, D; Pratt, F (2010)
We present the results of muon-spin relaxation (μ+ SR) measurements on the hexagonal manganite HoMnO3. Features in the temperature-dependent relaxation rate λ correlate with the magnetic transitions at 76, 38, and 34 K. The highest temperature transition, associated with the ordering of Mn3+ moments has the largest effect on λ. The application of a static electric field of E=5× 106 Vm-1 below T=50K causes a small reduction in λ which is suggestive of coupling between ferroelectric and magnetic domain walls in the ordered state of the material. © 2010 The American Physical Society.